Competition, premature trading and excess volatility - Deb, Pragyan; Koo, Bonsoo; Liu, Zijun (Journal of Banking & Finance, 2014)
A substantial body of research suggests that it is difficult to account for all of the volatility of asset prices in terms of news. This paper attempts to explain the excess volatility puzzle as a consequence of competitive interaction between market participants in the presence of noisy information. We develop a model of competitive interaction between market participants in response to unverified information. Our model shows that in the presence of competitive pressures, market participants find it optimal to act prematurely on unverified information. This premature reaction leads to lower total profits and excess market volatility in equilibrium. Our model also shows that the spike in volatility at the closing time of the market can be modelled as a direct consequence of premature trading.